Doping attitudes and covariates of potential doping behaviour in high-level team-sport athletes; Gender specific analysis - Sekulic, D.; Tahiraj, E.; Zvan, M.; Zenic, N.; Uljevic, O.; Lesnik, B. (Journal of Sports Science & Medicine, 2016)
Team sports are rarely studied with regard to doping behaviour and doping-related factors regardless of their global popularity. This study aimed to investigate doping factors and covariates of potential doping behaviour in high-level team-sport athletes. The subjects were 457 high-performing, national- and international-level athletes (21.9 ± 3.4 years of age; 179 females) involved in volleyball (n = 77), soccer (n = 163), basketball (n = 114) and handball (n = 103). Previously validated self-administered questionnaires aimed at evidencing sport factors, doping-related factors, knowledge on sport nutrition and doping, and attitudes to performance enhancement were used. The results indicated a higher doping likelihood in male athletes, with a significant gender difference for basketball and handball. In males, a higher doping likelihood is found for athletes who had achieved better results at junior-age level, those who regularly consume dietary supplements, and who perceive their sport as being contaminated by doping. A higher sport achievement at senior-age level is protective against potential doping behaviour in males. In females, a higher likelihood of doping is evidenced in those athletes involved in binge drinking, while a lower tendency for doping is evidenced in female athletes who possess better knowledge on sport nutrition. Knowledge about doping is very low and thus education about doping is urgently needed. An improvement of knowledge on sport nutrition might be a potentially effective method for reducing the tendency for doping in females. Future studies should consider other approaches and theories, such as theory of planned behaviour and/or social-cognitive theory, in studying the problem of doping behaviour in team-sports.